Simulating asteroid impacts and meteor events by high-power lasers: from the laboratory to spaceborne missions - Ferus, Martin; Knížek, Antonín; Cassone, Giuseppe; Rimmer, Paul B.; Changela, Hitesh; Chatzitheodoridis, Elias; Uwarova, Inna; Žabka, Ján; Kabáth, Petr; Saija, Franz; Saeidfirozeh, Homa; Lenža, Libor; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Meteor plasmas and impact events are complex, dynamic natural phenomena. Simulating these processes in the laboratory is, however, a challenge. The technique of laser induced dielectric breakdown was first used for this purpose almost 50 years ago. Since then, laser-based experiments have helped to simulate high energy processes in the Tunguska and Chicxulub impact events, heavy bombardment on the early Earth, prebiotic chemical evolution, space weathering of celestial bodies and meteor plasma. This review summarizes the current level of knowledge and outlines possible paths of future development.